Integrin‐linked kinase regulates tubular aquaporin‐2 content and intracellular location: a link between the extracellular matrix and water reabsorption. Issue 8 (1st May 2014) - Cano‐Peñalver, Jose Luis; Griera, Mercedes; Serrano, Isabel; Rodríguez‐Puyol, Diego; Dedhar, Shoukat; de Frutos, Sergio; Rodríguez‐Puyol, Manuel
Abstract : One of the clinical alterations observed in chronic renal disease (CRD) is the impaired urine concentration, known as diabetes insipidus (DI). Tubulointerstitial fibrosis of the kidney is also a pathological finding observed in CRD and involves composition of extracellular matrix (ECM). However, an association between these two events has not been elucidated. In this study, we showed that the extracellular‐to‐intracellular scaffold protein integrin‐linked kinase (ILK) regulates expression of tubular water channel aquaporin‐2 (AQP2) and its apical membrane presence in the renal tubule. Basally, polyuria and decreased urine osmolality were present in ILK conditional‐knockdown (cKD‐ILK) adult mice compared with nondepleted ILK littermates. No changes were observed in arginine‐vasopressin (AVP) blood levels, renal receptor (V2R), or AQP3 expression. However, tubular AQP2 was decreased in expression and apical membrane presence in cKD‐ILK mice, where the canonical V2R/cAMP axis activation is still functional, but independent of the absence of ILK. Thus, cKD‐ILK constitutes a nephrogenic diabetes insipidus (NDI) model. AQP2 and ILK colocalize in cultured inner medullary collecting duct (mIMCD3) cells. Specific ILK siRNAs and collagen I (Col) decrease ILK and AQP2 levels and AQP2 presence on the membrane of tubular mIMCD3 cells, which impairs the capacity of the cells to transport water under hypotonic stress. The present work points to ILK as a therapeutic target in NDI.—Cano‐Peñalver, J. L., Griera, M., Serrano, I., Rodríguez‐Puyol, D., Dedhar, S., de Frutos, S., Rodríguez‐Puyol, M. Integrin‐linked kinase regulates tubular aquaporin‐2 content and intracellular location: a link between the extracellular matrix and water reabsorption. FASEB J. 28, 3645–3659 (2014). www.fasebj.org